Time to speed up, not slow down: A narrative review on the importance of community-based physical activity among older people - Robyn Hambrook; Geoff Middleton; Daniel C Bishop; Lee Crust; David R Broom (Journal of Health and Social Sciences)
Introduction: There is now substantial evidence that physical activity reduces the risk of falls and physical disability in later life. Despite encouragement, many older adults are not accruing the health benefits of an active lifestyle. The purpose of this review is to provide an update on the literature specifically highlighting the benefits of regular physical activity (PA) for older adults in the community setting. Methods: An exploratory, narrative review was constructed from peer-reviewed journal articles after a literature database search involving Google Scholar, SPORTDiscus, and PubMed. We considered all types of article and study design written in English language and published with a date range set between 2002 to 2018. Results: A multitude of benefits related to the effects of physical activity with older adults were recognised in the literature search. Two overarching thematical dimensions were formed to represent the findings of this review: 1) functional ability and independence, and 2) psychological health and social connectedness. Our findings showed that community-based group exercise programmes have been found to positively enhance older adult’s physical function, improving mobility and flexibility. The primary components related to successful ageing are: 1) The absence of disease and disability, 2) the maintenance of physical and cognitive function, and 3) continued involvement in social activities. Discussion: While the prescription and community-based programmes for older adults vary in format, structure and effectiveness, it is perhaps more important to promote the general concept of encouraging as many individuals to participate and adhere to sustained PA in later life, particularly as so many benefits are accrued from simply taking part.